Efficacy and safety of 2 Hz versus 100 Hz electroacupuncture for pain-dominant shoulder periarthritis: a study protocol for a single-center randomized controlled trial - Chengyu Liu; Shiwei Zhuang; Yi Shang; Xiangzhen Miao; Hongfeng Wang; Bing Yan (Frontiers in Medicine, 2026)
Background Pain-dominant shoulder periarthritis is characterized by shoulder pain, restricted range of motion (ROM), and impaired daily function. Electroacupuncture (EA) is a controllable acupuncture modality used for shoulder pain disorders; however, direct evidence comparing 2 Hz and 100 Hz EA in this disease stage remains limited. Objective This study aims to compare the efficacy and safety of low-frequency EA (2 Hz) and high-frequency EA (100 Hz) for pain-dominant shoulder periarthritis. Methods This is a single-center, participant- and outcome assessor-blinded, parallel-group randomized controlled trial (RCT) to be conducted at the Third Clinical Hospital Affiliated to Changchun University of Chinese Medicine. A total of 152 participants who meet the diagnostic criteria for pain-dominant shoulder periarthritis and the traditional Chinese medicine (TCM) meridian differentiation criteria for the Hand Shaoyang meridian pattern will be enrolled. Participants will be randomly assigned in a 1:1 ratio to the 2 Hz EA group or the 100 Hz EA group. Both groups will receive the same acupuncture prescription, treatment procedures, and co-interventions, with EA frequency as the only planned between-group difference. Treatment will be administered once daily for 5 consecutive days per course, with a 2-day interval between courses, for a total of 10 sessions. Outcomes will be assessed at baseline and at 2, 8, and 24 weeks after treatment initiation. The primary outcome will be overall shoulder pain intensity measured using a 10-cm visual analog scale (VAS) at T1. The primary comparison will be the adjusted mean difference in the T1 overall VAS score between the two groups, with baseline overall VAS included as a covariate. Secondary outcomes will include component-specific VAS ratings for resting pain, activity-related pain, and nocturnal pain, the Shoulder Pain and Disability Index (SPADI), the Constant-Murley Score (CMS), and shoulder ROM. Adverse events (AEs) and serious adverse events (SAEs) will be recorded throughout the study. Discussion This trial may provide clinical evidence to inform EA frequency selection and parameter standardization for pain-dominant shoulder periarthritis. Clinical trial registration International Traditional Medicine Clinical Trial Registry, https://itmctr.ccebtcm.org.cn , identifier ITMCTR2026000862.